Study of soil infiltration rate in some land uses at Desa Tanjung Putus Kecamatan Padang Tualang Kabupaten Langkat - Sri Puspita Sari; Sumono .; Nazif Ichwan; Edi Susanto (Universitas Sumatera Utara, 2013)
The aim of this research was to know the infiltration rate and matrix potential in some land uses; i.e. field, rubber field, and bush at Desa Tanjung Putus Kecamatan Padang Tualang Kabupaten Langkat using Philips equation model. Parameters that perceived were moisture content, soil texture, bulk density, particle density, porosity, and organic matter. This research used double ring infiltrometer and observed for 240 minutes. The results showed that the biggest infiltration rate was found in rubber field , and bush ; the smallest was found in field . The matrix potential in that lands were become smaller by the increasing of soil moisture.